Centrifugal disc liquid reciprocation flow considerations for antibody binding to COVID antigen array during microfluidic integration. Issue 14 (23rd June 2022) - Hwu, Alexander T.; Madadelahi, Masoud; Nakajima, Rie; Shamloo, Ehsan; Perebikovsky, Alexandra; Kido, Horacio; Jain, Aarti; Jasinskas, Algis; Prange, Shawna; Felgner, Philip; Madou, Marc
Abstract : Investigating fluid flow behavior during different acceleration and deceleration ramp rates for immunoassays. Abstract : Heterogeneous immunoassays (HI) are an invaluable tool for biomarker detection and remain an ideal candidate for microfluidic point-of-care diagnostics. However, automating and controlling sustained fluid flow from benchtop to microfluidics for the HI reaction during the extended sample incubation step, remains difficult to implement; this leads to challenges for assay integration and assay result interpretation. To address these issues, we investigated the liquid reciprocation process on a microfluidic centrifugal disc (CD) to generate continuous, bidirectional fluid flow using only a rotating motor. Large volumetric flow rates (μL s −1 ) through the HI reaction chamber were sustained for extended durations (up to 1 h). The CD liquid reciprocation operating behavior was characterized experimentally and simulated to determine fluid flow shear rates through our HI reaction chamber. We demonstrated the continuous CD liquid reciprocation for target molecule incubation for a microarray HI and that higher fluid shear rates negatively influenced our fluorescence intensity. We highlight the importance of proper fluid flow considerations when integrating HIs with microfluidics.